Partisipasi Kelompok Tani dalam Kegiatan Usahatani Padi untuk Mendukung Pertanian Berkelanjutan: Participation of Farmer Groups in Rice Farming Activities to Support Sustainable Agriculture - Silaban, Budi; Asaad, Mhd; Sitepu, Rasidin Karo Karo (Journal of Integrated Agribusiness, 2025)
Farmer involvement refers to the active participation of individual farmers or farmer collectives in decision-making processes with awareness and intention. This study examines the extent of farmer engagement in sustainable agricultural practices. Descriptive statistics were used to profile respondents, while the Structural Equation Modeling (SEM) approach was applied to assess the effect of participation in farmer groups on sustainable agriculture. Sixty rice farmers were selected as respondents using the Slovin formula. The research was conducted in the Secanggang District, Langkat Regency, a key rice-producing area deliberately chosen as the study site. Primary data were collected through a structured questionnaire. The analysis revealed that among the three dimensions of sustainability, social, economic, and environmental, only the financial and ecological aspects showed statistically significant effects, with coefficients of 0.398 and 0.502, respectively. Farmer participation in evaluation and implementation processes contributed positively to advancing sustainable agricultural practices. Strengthening farmer groups should be prioritized by government agencies and academic institutions, with efforts directed toward enhancing human resource capacity in areas such as institutional management, market network expansion, partnership development, capital strengthening, and information technology training.